Representações sociais da disciplina Química entre alunos dos centros de excelência de Aracaju - Silva, Fernando Antônio Nascimento da (2011)
Chemistry is taken, in the words of a significant portion of high-school students, as "difficult, complicated and boring", causing various manifestations of discontent among students, when the need to study it. This research proposes the investigation of this relationship between this subject and the students, according to the Theory of Social Representations. It is proposed to identify the social representations of chemistry subjects in the individuals studied, the influence of social representations over the relation of students participating in the research and chemistry with differences and similarities, with regard to social representations, there are between the schools in study. Methodologically, we chose to use focus groups with students from the two Centers of Excellence located in Aracaju, to collect the data necessary to accomplish the study. The results demonstrate the construction of social representations which show that the distance of students toward the subject arises, significantly, because of the need for greater investment in their study, without, however, the guarantee of their learning.